Vietnam : 2003 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Vietnam. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
Vietnam's macroeconomic performance has been strong, fueled by strong export performance, poverty reduction, and domestic investment. Executive Directors welcomed this development, and stressed the need for strong monetary, exchange rate, and fiscal policies. They appreciated the prudent macroeconomic management, and the transformation from a planned to a market economy. They welcomed the passage of the new Statistics Law, and Vietnam's participation in the IMF's General Data Dissemination System, and emphasized the need to implement public administration and structural reform programs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet